Heat Stress Impairs Endometrial Function During Implantation by Regulating Autophagy in Hainan Black Goat - Xiaoping Li; Yanyu Sun; Yi Min; Xinyu Wang; Diqi Yang; Hui Peng (Animals)
Heat stress (HS) is a significant factor that adversely affects the health, welfare, and productivity of domestic animals, particularly impacting embryo implantation rates. However, the effects of HS on endometrial function during the peri-implantation period in Hainan black goats remain unclear. This study explores the influence of HS on the endometrium of these goats. We collected uterine tissue samples from both control and heat-stressed goats and performed in vitro experiments using a 2 × 2 factorial design. This design included two temperature conditions (37 °C as the control and 42 °C to simulate heat stress) and two pharmacological treatments: chloroquine (CQ), an autophagy inhibitor, and rapamycin (RAPA), an autophagy activator. Our results showed that heat stress initially suppresses autophagy activity, which is subsequently enhanced with prolonged exposure. The pharmacologic modulation of autophagy, through activation or inhibition, resulted in corresponding upregulation or downregulation of the endometrial epithelial cells’ (EECs) receptivity markers. The overexpression of ATG7 partially reversed the HS-induced downregulation of these markers. Additionally, TJP1, a tight-junction marker, was degraded under the pharmacologic and genetic activation of autophagy in HS conditions but accumulated more in the EECs pre-treated with CQ. These findings suggest that autophagy plays a protective role in maintaining endometrial function under HS conditions in Hainan black goats. This study offers valuable insights into the role of autophagy in endometrial receptivity and proposes a potential strategy to mitigate the adverse effects of HS on goat reproduction.